Influence of Price Increases, Product Availability, and Service Quality on Consumer Satisfaction (A Case Study at LPG 3 Kg Distribution Point Yulianto, agent of PT Mita Ereska, Semarang Regency) - Dita Ratna Sari; Sri Wahyuni; Paniya (Politeknik Negeri Semarang, 2025)
Liquefied Petroleum Gas (LPG) 3 kg is an essential basic need for low- to middle-income communities in Indonesia. Price increases, limited product availability, and service quality are factors that can affect consumer satisfaction with this subsidized product. This study aims to analyze the influence of price increases, product availability, and service quality on consumer satisfaction at distribuiton point LPG 3 kg Yulianto, an agent of PT Mita Ereska in Semarang Regency. The research used a quantitative method with a multiple linear regression approach. Data were collected through questionnaires distributed to 89 respondents. The results show that price increases have a negative and significant effect on consumer satisfaction, while product availability and service quality have a positive and significant effect. The regression equation obtained is Y = 4.361 − 1.375X1 + 1.834X2 + 1.308X3. The significance values from both the t-test and F-test are < 0.05, indicating that all three variables have a significant effect both partially and simultaneously. The Adjusted R Square value of 0.513 indicates that 51.3% of the variation in consumer satisfaction is explained by the three independent variables, while the remaining 48.7% is influenced by other factors not examined in this study. The study concludes that improving service quality and managing product availability are essential to maintaining consumer satisfaction despite price increases. Liquefied Petroleum Gas (LPG) 3 kg merupakan kebutuhan dasar bagi rumah tangga berpenghasilan rendah hingga menengah di Indonesia. Faktor-faktor seperti kenaikan harga, keterbatasan ketersediaan produk, dan kualitas layanan dapat memengaruhi kepuasan konsumen terhadap produk bersubsidi ini. Penelitian ini mengkaji pengaruh kenaikan harga, ketersediaan produk, dan kualitas layanan terhadap kepuasan konsumen di titik distribusi LPG 3 kg Yulianto, agen PT Mita Ereska di Kabupaten Semarang. Pendekatan kuantitatif dengan regresi linier berganda digunakan, dan data dikumpulkan dari 89 responden menggunakan kuesioner. Hasil penelitian menunjukkan bahwa kenaikan harga berpengaruh negatif terhadap kepuasan konsumen, sedangkan ketersediaan produk dan kualitas layanan berpengaruh positif. Model regresi menunjukkan bahwa ketiga variabel secara signifikan memengaruhi kepuasan konsumen baik secara individual maupun simultan. Nilai Adjusted R² sebesar 0,513 menunjukkan bahwa 51,3% variasi kepuasan konsumen dijelaskan oleh variabel-variabel ini, sedangkan 48,7% sisanya dipengaruhi oleh faktor-faktor lain. Temuan ini menyoroti pentingnya meningkatkan kualitas layanan dan mengelola ketersediaan produk untuk mempertahankan kepuasan konsumen meskipun terjadi kenaikan harga.